Towards Sustainable Workplaces: Green Atmospherics’ Influence on Employee Well-Being Mediated by Work Stress - I Wayan Satria Virgantara; Muhammad Irfan Syaebani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Urbanization has intensified the scarcity of green spaces and heightened psychological pressures in modern workplaces, underscoring the need for effective strategies to enhance employee well-being. This study investigates the influence of Green Spaces, Green Ambient Conditions, and Outdoor Green Environment on Employee Well-being, with Work Stress as a mediating variable. Using Covariance-Based Structural Equation Modelling (CB-SEM), data were collected from 315 office workers in Indonesia’s top 10 cities according to the 2024 Universitas Indonesia (UI) GreenCityMetric, reflecting high environmental sustainability. Results show Green Spaces have the strongest direct positive effect on Employee Well-being, while Green Ambient Conditions also contribute significantly. Outdoor Green Environment, however, does not directly affect well-being. Work Stress emerges as a key mediator, partially mediating the effect of Green Ambient Conditions and fully mediating the effect of Outdoor Green Environment on Employee Well-being. These findings highlight that fostering employee well-being requires a holistic approach, optimizing green spaces, enhancing ambient conditions, providing access to external green environments, and managing work stress, to create healthier, more sustainable workplaces.